Technology shifts in power electronics and electric motors for hybrid vehicles-A study of Silicon Carbide and iron powder materials - Horrdin, Henrik; Olsson, Eva (My University, 2007)
This thesis has been conducted together with Volvo Powertrain, Hybrid Technology. The purpose is to see if technology shifts for power electronics and electric motors in heavy hybrid vehicles could be advantageous, compared to today’s silicon (Si) based semiconductors and laminated steel based motors. The semiconductor material, which was examined, was silicon carbide (SiC) and for the electric motor the powder materials soft magnetic composites (SMC) and plastic bonded iron powder (PBIP) were examined. The data was collected through articles and interviews. SiC has the ability to operate at high temperatures (up to 600°C) with a ten times higher breakdown voltage than that of Si. The switching speed can be higher, due to low capacitance in the devices. Losses are considerably low during turn-on and turnoff, because the reverse recovery is extremely small. Problems with SiC are wafer quality, gate isolation and packaging material. Several companies and universities are developing SiC technology, but still the leading actors are Cree and Infineon. The quality of SiC wafers is improving, but the size of the wafer is today small for good quality, maximum 3", while Si wafers of good quality can be up to 12". Iron powder materials can be moulded to motor parts for the magnetic flux paths. The relative permeabilities (magnetic conductivity) are as low as 700 for SMC and 20 for PBIB, compared to 8000 for laminated steel. Despite this, the performance of the motors might be acceptable with a 3D design where the magnetic flux paths are shorter or where other benefits arise. The profit would be in lower manufacturing costs due to less manufacturing steps and less material waste during manufacturing. A negative impact of SMC is that it has more losses than steel sheets up to 1000 Hz. For PBIP no result has been noticed yet. Conclusions that have been drawn are that a shift in the future to SiC in hybrid vehicles would reduce cooling equipment, size of passive components, losses and space. Taken together this could reduce the total cost. For the iron powder materials no conclusions about if they are profitable to use in electric motors can be
Keywords: Elkraftteknik; Electric power engineering